2014
DOI: 10.1016/j.cell.2014.05.048
|View full text |Cite
|
Sign up to set email alerts
|

Autophagic Clearance of PolyQ Proteins Mediated by Ubiquitin-Atg8 Adaptors of the Conserved CUET Protein Family

Abstract: Selective ubiquitin-dependent autophagy plays a pivotal role in the elimination of protein aggregates, assemblies, or organelles and counteracts the cytotoxicity of proteins linked to neurodegenerative diseases. Following substrate ubiquitylation, the cargo is delivered to autophagosomes involving adaptors like human p62 that bind ubiquitin and the autophagosomal ubiquitin-like protein Atg8/LC3; however, whether similar pathways exist in lower eukaryotes remained unclear. Here, we identify by a screen in yeast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
356
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 299 publications
(368 citation statements)
references
References 53 publications
8
356
2
2
Order By: Relevance
“…For example, the autophagy cargo receptors p62 (also known as SQSTM1), NBR1 (next to BRCA1 gene 1 protein) and histone deacetylase 6 (HDAC6) all promote the autophagic clearance of protein aggregates in a process known as aggrephagy, which is dependent on both the UBD and LIR 2,10 . In yeast, although orthologues of UBD-containing adaptor proteins such as p62 are missing, a recent mass spectrometric study identified Cue5 as a potential autophagy cargo receptor 23 . Cue5 possesses a coupling of ubiquitinconjugation to ER degradation (CUE) domain, which is structurally related to mammalian UBDs and is capable of binding to ubiquitin as well as interacting with Atg8.…”
Section: Overview Of the Autophagic Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the autophagy cargo receptors p62 (also known as SQSTM1), NBR1 (next to BRCA1 gene 1 protein) and histone deacetylase 6 (HDAC6) all promote the autophagic clearance of protein aggregates in a process known as aggrephagy, which is dependent on both the UBD and LIR 2,10 . In yeast, although orthologues of UBD-containing adaptor proteins such as p62 are missing, a recent mass spectrometric study identified Cue5 as a potential autophagy cargo receptor 23 . Cue5 possesses a coupling of ubiquitinconjugation to ER degradation (CUE) domain, which is structurally related to mammalian UBDs and is capable of binding to ubiquitin as well as interacting with Atg8.…”
Section: Overview Of the Autophagic Pathwaymentioning
confidence: 99%
“…Hence, Cue5 is a ubiquitin-Atg8 adaptor protein that functions analogously to p62 in mammals to mediate the selective autophagic degradation of ubiquitylated targets. Both yeast Cue5 and its mammalian orthologue, Toll interacting protein (TOLLIP), target aggregationprone proteins that cannot be cleared by the UPS, such as huntingtin, for autophagic degradation 23 .…”
Section: Overview Of the Autophagic Pathwaymentioning
confidence: 99%
“…Instead, Cue5 has been identified as selective autophagy receptor for ubiquitinated proteasomes in yeast. Cue5 and its human homolog Tollip have been implicated only recently in the autophagic clearance of polyQ proteins (11). Moreover, proteaphagy in yeast requires the action of the chaperone Hsp42.…”
mentioning
confidence: 99%
“…Autophagy receptors link selective cargos to the core autophagy machinery, especially to the Atg8 protein. At least eight autophagy receptors have been identified in fungal species: S. cerevisiae Atg19 and Atg34 for the Cvt pathway (Leber et al, 2001;Scott et al, 2001;, S. cerevisiae Atg30 and P. pastoris Atg36 for pexophagy (Farré et al, 2008;Motley et al, 2012), S. cerevisiae Atg32 for mitophagy (Kanki et al, 2009a;Okamoto et al, 2009), S. cerevisiae Atg39 for nucleophagy (Mochida et al, 2015), S. cerevisiae Atg40 for ER-phagy (Mochida et al, 2015) and S. cerevisiae Cue5 for aggrephagy (Lu et al, 2014). Among these receptors, only Cue5 has an obvious S. pombe homolog (SPBC16E9.02c), which is a yet uncharacterized protein.…”
Section: Discussionmentioning
confidence: 99%